A Microbial-Based Biostimulant Enhances Sweet Pepper Performance by Metabolic Reprogramming of Phytohormone Profile and Secondary Metabolism - Bonini, Paolo; Rouphael, Youssef; Miras-Moreno, Begoña; Lee, Byungha; Cardarelli, Mariateresa; Erice, Gorka; Cirino, Veronica; Lucini, Luigi; Colla, Giuseppe (Frontiers in Plant Science, 2020)
Microbial-based biostimulants can improve crop productivity by modulating cell metabolic pathways including hormonal balance. However, little is known about the microbial-mediated molecular changes causing yield increase. The present study elucidates the metabolomic modulation occurring in pepper (Capsicum annuum L.) leaves at the vegetative and reproductive phenological stages, in response to microbial-based biostimulants. The arbuscular mycorrhizal fungi Rhizoglomus irregularis and Funneliformis mosseae, as well as Trichoderma koningii, were used in this work. The application of endophytic fungi significantly increased total fruit yield by 23.7% compared to that of untreated plants. Multivariate statistics indicated that the biostimulant treatment substantially altered the shape of the metabolic profile of pepper. Compared to the untreated control, the plants treated with microbial biostimulants presented with modified gibberellin, auxin, and cytokinin patterns. The biostimulant treatment also induced secondary metabolism and caused carotenoids, saponins, and phenolic compounds to accumulate in the plants. Differential metabolomic signatures indicated diverse and concerted biochemical responses in the plants following the colonization of their roots by beneficial microorganisms. The above findings demonstrated a clear link between microbial-mediated yield increase and a strong up-regulation of hormonal and secondary metabolic pathways associated with growth stimulation and crop defense to environmental stresses.